The portrait of prospective mathematics teachers in critical thinking through problems with contradictory information: A view from prior knowledge - Wulan, Eka Resti; Rahayu, Dwi Shinta; El Milla, Yulia Izza; Araiku, Jeri (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: The development of critical thinking skills in prospective mathematics teachers is essential for their future effectiveness in the classroom. Understanding how these individuals process and resolve problems that contain contradictory information provides insight into their critical thinking abilities. Previous research has highlighted the significant role of prior knowledge in problem-solving and critical thinking.Aim: This study aims to explore the critical thinking processes of prospective mathematics teachers when faced with problems that contain contradictory information. Specifically, it seeks to determine the influence of prior knowledge on their ability to navigate and resolve these complex problems.Methods:  The study employed a sequential explanatory design. Initially, quantitative data from prerequisite skill and critical thinking tests (specifically, problems with contradictory information) were collected from 68 participants. Simple regression analysis informed the selection of six participants (two each with high, medium, and low prerequisite abilities) for the subsequent qualitative phase. In-depth interviews and problem-solving tasks were conducted, prompting participants to articulate their thought processes. Data analysis focuses on identifying patterns and themes in their use of prior knowledge and critical thinking strategies.Results: The findings reveal that prior knowledge plays a pivotal role in how prospective mathematics teachers approach and resolve problems with contradictory information. Those with a strong foundation in mathematical concepts and problem-solving strategies are better equipped to identify inconsistencies and develop logical solutions. Conversely, participants with limited prior knowledge struggle to reconcile conflicting information and often resort to less effective problem-solving methods.Conclusion: This study underscores the importance of prior knowledge in the development of critical thinking skills among prospective mathematics teachers. Educator preparation programs should emphasize the cultivation of a robust knowledge base and provide opportunities for students to engage in complex problem-solving tasks. By doing so, future teachers will be better prepared to navigate the challenges of the classroom and foster critical thinking in their own students.